1989
DOI: 10.1254/jjp.50.253
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of eicosanoid-induced contraction of mouse and rat blood vessels by gingerols.

Abstract: Abstract-The effects of the active principles of crude ginger (a traditional Sino Japanese medicine), the gingerols, on the contractile responses to eicosanoids were compared using isolated mouse and rat blood vessels. Leukotrienes (LT) C4 and D4, a thromboxane (TX) A2 derivative (U-46619), prostaglandins (PG) F2a, PG12-Na, PGE2, the stable PG12 derivative TRK-100, and PGD2 induced con traction in longitudinal segments of mouse mesenteric veins in that order of potency. Exogenous arachidonic acid and PGE, did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This demonstrates the presence of receptors for each eicosanoid in the venous smooth muscle (24). The in fluence of diabetes on the synthesis of prostanoids has been reported, suggesting decreased prostacyclin production and in creased TX synthesis (10,25).…”
Section: Discussionsupporting
confidence: 56%
“…This demonstrates the presence of receptors for each eicosanoid in the venous smooth muscle (24). The in fluence of diabetes on the synthesis of prostanoids has been reported, suggesting decreased prostacyclin production and in creased TX synthesis (10,25).…”
Section: Discussionsupporting
confidence: 56%
“…It is possible that the polyphenol gingerol had induced phase-II detoxifying and antioxidant enzymes via activation of Keap1-Nrf2-ARE. Previous studies showed that (+/−)- [5]-gingerols inhibited the contractions in isolated rat blood vessels, induced by prostanoids PGD-2, TXA-2, and LT, suggesting the modulation of eicosanoids-induced responses by these compounds also [29]. Previous studies showed that (+/−)- [5]-gingerols inhibited the contractions in isolated rat blood vessels, induced by prostanoids PGD-2, TXA-2, and LT, suggesting the modulation of eicosanoids-induced responses by these compounds also [29].…”
Section: Discussionmentioning
confidence: 96%
“…23 To assess the per se effect of gingerol, rat aortic rings were incubated with a wide range of concentrations of gingerol (30-300 mmol/L), which was based on the previous published reports. 24,25 Gingerol was incubated for 30 minutes and dose-response of PE (1-100 mmol/L) was monitored. To assess the per se effect of gingerol (3-300 mmol/L) for their vasorelaxant efficacy, responses were obtained in PE (1 mmol/L) precontracted endothelium intact rings.…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 99%